A strong-form Chebyshev-RPIM meshless solution for free vibration of conical shell panels with variable thickness and fiber curvature. (15th September 2022) - Hu, Shuangwei; Zhong, Rui; Wang, Qingshan; Qin, Bin; Shao, Wen
Abstract: This paper provides a strong-form meshless method for free vibration analysis of curved panels with variable thickness and variable fiber curvature, such as cylindrical, conical and sector panels. Under the framework of the first-order shear deformation theory(FSDT), the Hamilton's principle is used to obtain the governing and boundary equations of the structure. The displacement allowance function is jointly constructed by Chebyshev polynomials and radial interpolation functions. The control and the boundary equations are discretized using meshless technology. The validity of the proposed model is verified by comparison with the results of existing literature and finite element software. On this basis, the influence of thickness parameters, fiber variation parameters and boundary conditions on the dynamic characteristics of the structure is studied. The method and systematic numerical analysis results presented in this study are helpful to lay a scientific foundation and provide an engineering guidance for the in-depth understanding and prediction of vibration characteristics of similar structures.